Use of mobile telecommunication data in transport modelling: A French case study - Imane Essadeq; Thibault Janik (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2021)
Transport planners see an opportunity in mobile phone data to better map trip destinations and monitor travel demand over time. However, such data require extensive processing to reveal trip details and transport modes. This paper defines quality indicators for reliable trip data collection and examines sensitivity to key parameters. It compares the trip matrices resulting from mobile network data with independent sources. This paper concludes on the strengths and weaknesses of such data in various transport planning tasks.
Keywords: 330